Konferencje i szkolenia online zorganizowane w Polsce w latach 2020–2021 (wybór) - Kowalska, Marzena (Acta Universitatis Lodziensis. Folia Librorum, 2021)
Selective list of conferences and trainings in the field of information and book science, as well as social communication and media, which were held online in Poland during the pandemic in 2020–2021. National and international events have been registered.